RIBA DALAM TRANSAKSI KEUANGAN - JAIH MUBAROK (At-Taradhi Jurnal Studi Ekonomi, 2015)
Abstract: The doctrine of riba is one of the important teachings of related transactions in accordancewith Islamic principles. In sharia science, among sharia-compliant transaction is a transaction that isprotected from the elements of riba, gharar, gambling, dharar, and zhulm. This study successfully dem-onstrated the arguments Prohibition of riba and the formation of a variety of riba: 1) riba Fadl (due tonon-fulfillment of the provisions sawa [ an] bi saawa [in]); 2) riba nasa (due to non-fulfillment of theprovisions mitsl [ an] bi mitsl [in]); and 3) nasiah riba (because akumluasi the form of non-fulfillmentof the relevant provisions sawa [ an] bi saawa [in]) and mitsl [ an] bi mitsl [in]). Another Riba is foundin the history of riba jahiliah and riba qardh. In the context of financial transactions, interest cash/bankincluding nasiah riba.